PENGARUH PERSEPSI PEGAWAI MENGENAI OUTSOURCING TERHADAP KEPUASAN KERJA DAN TURNOVER INTENTION - Retno Sari Murtiningsih (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
The Background of this research was the trend of companies’ outsourcing human resource (expertise and specialists) to accomplish tasks more cheaply and efficiently to increase productivity. The objective of this research was to find out the impact of employees’ perception of outsourcing human resource on their job satisfaction and turnover intention. To achieve this objective the quantitative research has been done by using explanatory survey method. The design of thisresearch applies quantitative approach. The samples for the study consisted of 115 human resource division employees of three Banks in Jakarta. The primary data in this research was obtained by using closed ended questionnaires. Non probability sampling method with the convenience sampling technique was employed to select the sample. Data analysis used in this research was Structural Equation Modeling (SEM). The result of this research concludes that employees’ positive perception of outsourcing human resource increases their job satisfactionand decreases their turnover intention whereas negative perception of outsourcing human resource decreases job satisfaction and subsequently increases turnover intention. Based on the result of the research, it is important that a company outsource human resource to increase productivity.